The First Example of Azole-Fused Cyclic Anhydride Reacting in the Castagnoli–Cushman Way - Moreau, Ella; Dar’in, Dmitry; Krasavin, Mikhail (Synlett, 2018)
Pyrazole-fused cyclic anhydrides have been employed for the first time as the Castagnoli–Cushman reaction partners to produce hitherto unknown 4-oxo-4,5,6,7-tetrahydropyrazolo[1,5-a]pyrazine-7-carboxylates in remarkably convenient and speedy fashion. Attempts to realize the same chemistry with indole and benzimidazole analogues failed.
Keywords: multicomponent reactions; Castagnoli–Cushman reaction; nonstabilized enolate; pyrazole-fused; cyclic anhydrides